Pelatihan Akuntansi, Pajak dan Kewirausahaan pada Pondok Pesantren Nurul Ihsan Sebagai Alternatif Pemberdayaan Masyarakat Mandiri - Kamaliyah, Fithrah; Agustini, Sri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This Community Service aims to develop knowledge such as accounting, tax and entrepreneurship so that students will be able to compete in the world of work and also be able to open a business so they can be economically independent. The method used in this PKM is based on teaching and entrepreneurial practice in making products in the form of traditional food which can be sold later to earn additional income for the students of the Nurul Ihsan Islamic Boarding School. As a result of this PKM, students are very motivated to learn more about accounting and taxes, and are also motivated to open businesses independently in order to get additional income that can be used as pocket money or savings to continue their education to a higher level.